APPLICATION OF ROLE PLAY LEARNING TO IMPROVE THE ATTITUDE OF NATIONAL CULTURE DIVERSITY OF ELEMENTARY SCHOOL STUDENTS - Awiria Awiria; Ujang Jamaludin (JPSD (Jurnal Pendidikan Sekolah Dasar), 2020)
AbstractThis study aims to improve the students’ cultural diversity based on the application of role playing learning models in elementary schools. This type of research is classroom action research, conducted in two cycles. The data is collected by observation and questionnaire techniques. This research was conducted on fourth grade students of 33 students. The success of the research is determined by the class average score that must be at least 70. The obtained data were analyzed descriptively. The results showed that there was an increase in the students' cultural diversity from first cycle to second cycle. The results showed a change in cultural diversity attitudes of elementary school children after role playing learning, where students could respect and appreciate the differences of cultural, ethnic, racial, and regional language of students. Role playing learning can be applied in elementary schools to improve the national cultural diversity attitude of students.Keywords: Cultural Diversity; Multicultural; Role Playing